2016
DOI: 10.1016/j.ultsonch.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modification time and high frequency ultrasound irradiation on self-assembling of alkylphosphonic acids on stainless steel: Electrochemical and spectroscopic studies

Abstract: Self-assembly of alkylphosphonic acids on stainless steel was investigated under different conditions. Four different alkylphosphonic acids exhibiting alkyl chain of various size were synthesized and studied: butylphosphonic acid (C4P), octylphosphonic acid (C8P), decylphosphonic acid (C10P), and hexadecylphosphonic acid (C16P). Electrochemistry experiments were extensively carried out in order to determine electrochemical surface blocking of adsorbed layers in function of grafting time. In term of surface blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The first of these includes works in which the protective properties of APhs with a relatively small alkyl length, C 7 -C 10 , were studied, which made it possible to obtain their thin layers, including SAMs, in aqueous solutions [16][17][18][19][20][21][22][23][24][25][26]. In the second group more hydrophobic monophosphonic compounds were studied, mainly octadecylphosphonic acid (APhC 18 ), that cannot be applied from aqueous solutions [27][28][29][30][31][32][33]. The APhs from the first group adsorbed from aqueous solutions form protective layers on iron surface, which can suppress the dissolution of the metal and stabilize its passive state.…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these includes works in which the protective properties of APhs with a relatively small alkyl length, C 7 -C 10 , were studied, which made it possible to obtain their thin layers, including SAMs, in aqueous solutions [16][17][18][19][20][21][22][23][24][25][26]. In the second group more hydrophobic monophosphonic compounds were studied, mainly octadecylphosphonic acid (APhC 18 ), that cannot be applied from aqueous solutions [27][28][29][30][31][32][33]. The APhs from the first group adsorbed from aqueous solutions form protective layers on iron surface, which can suppress the dissolution of the metal and stabilize its passive state.…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 99%
“…Recently, in another work [28] the influence of the processing time of 304L stainless steel by ethanol solutions of 5.0 mM APhC 4 , APhC 8 , APhC 10 or APhC 16 was studied in order to determine the optimal conditions for the formation of SAM. It was found that the best results, judging from the cyclic voltammetry curves recorded in an aqueous solution containing 0.2 M Na 2 SO 4 and 5 mM K 4 [Fe(CN) 6 ], were obtained at 8 h in APh solutions.…”
Section: Mono-and Diphosphonic Acids and Their Saltsmentioning
confidence: 99%
“…The affinity between the reactive group and the substrate is of prime importance for ensuring efficient chemisorption on the surface. Many types of SAMs exhibiting various reactive headgroups (thiols [6] , phosphonic [7] , [8] , carboxylic [9] , [10] ) have been grafted on gold [11] , titanium [12] , copper [13] or stainless steel [14] to name just a few.…”
Section: Introductionmentioning
confidence: 99%
“…between 16 and 24 h, which renders industrial applications very difficult. In an attempt to solve this problem, some studies on the use of ultrasound to accelerate SAM grafting process have been carried out [11] , [14] , [18] , [19] , [20] . The studies by Atobe et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation